A strain defined as a novel species in the Acinetobacter genus co-harboring chromosomal associated tet(X3) and plasmid associated blaNDM-1 from a beef cattle farm in Hebei, China - Wang, Qing; Wei, Yanming; Shoaib, Muhammad; Qiu, Yanhua; Zhang, Chao; Dai, Guonian; Lin, Honglin; Wang, Weiwei; Zhang, Jiyu (Frontiers in Cellular and Infection Microbiology, 2025)
IntroductionThe co-existence phenomenon of antibiotic resistance genes (ARGs), particularly of last-resort antibiotics in multi-drug resistant (MDR) bacteria, is of particular concern in the least studied bacterial species.MethodsIn 2023, strain M2 was isolated from the sludge sample at a commercial bovine farm in Hebei province, China, using a MacConkey plate containing meropenem. PCR amplification and Sanger sequencing verified it co-carrying blaNDM and tet(X) genes. It was classified within the Acinetobacter genus by MALDI-TOF-MS and 16S rDNA analyses. Whole-genome sequencing (WGS) was performed on the Oxford Nanopore platform, with species-level identification via ANI and dDDH. Antimicrobial susceptibility testing was performed against 20 antibiotics. Conjugation assays employed the filter-mating method using E. coli J53 and Salmonella LGJ2 as recipients.ResultsThis strain was confirmed as a novel species of Acinetobacter genus, showing resistance to meropenem, ampicillin, ceftazidime, cefepime, gentamicin, kanamycin, fosfomycin, imipenem, ertapenem, and tetracycline. Despite carrying tet(X3), it remained susceptible to tigecycline, omadacycline, and doxycycline. The genome carried 11 ARG types, multiple metal resistance genes (MRGs), and virulence factor (VF) genes. The blaNDM-1 was located in a skeleton, ISAba125-blaNDM-1-bleMBL-trpF, which was carried by an ISAba14-mediated rolling-circle-like structure in pM2-2-NDM-1 (rep_cluster_481). Integrative and conjugative element (ICE) and multiple pdif modules (driven by the XerCD site-specific recombination (XerCD SSR) system), which were associated with the mobilization of resistance determinants, were identified in this plasmid. Chromosomal tet(X3) was mediated by ISVsa3, forming a skeleton, ISVsa3-XerD-tet (X3)-res-ISVsa3.DiscussionThe co-occurrence of blaNDM and tet(X) in a novel species of the Acinetobacter genus hints that substantial undiscovered bacteria co-carrying high-risk ARGs are concealing in the agroecological system, which should cause particular concern.